Planning: A Glue for Development Coalitions? State Actors' Agency and Power Relationships in Urban Development Projects in Milan and Brussels - Conte, Veronica (PARTECIPAZIONE E CONFLITTO, 2021)
In this paper, I combine urban regime analysis and financialisation scholarships to uncover the role of planning and question the role of state actors in urban development processes. Through an analysis of CityLife in Milan and Tour and Taxis in Brussels, I argue that state actors have a strong agency in decision making as they own a critical resource: planning. My investigation reveals that, in projects characterised by uncertainty and internal conflicts, planning functions as a glue of development coalitions. Local governments mobilise it to bring together private and public interests, in order to achieve their agendas. Nevertheless, this glue function plays out differently in Milan and Brussels. While in Milan local administrations used planning to facilitate the anchoring of capital, in Brussels local governments enacted planning to shift the balance of power between them. This outcome reveals contextual differences that ultimately depend on local governance settings and planning systems. The comparison depicts the making of two different development regimes. CityLife indicates a financialised turn in governance, in which planning choices are driven mainly by economic – and financial – imperatives. Tour and Taxis symbolises an experimental entrepreneurial urban regime, a sort of "laboratory" to test new governance and planning frameworks.